Arithmetic Operation of Matrices

Algebra Level 1

Suppose that x x and y y satisfy the following equation:

( x y 2 1 ) ( x 0 y x ) = 2 ( 10 6 x 3 0 ) + ( 5 2 x 4 x ) . \left(\begin{array}{cc}x& y \\2&1 \end{array}\right)\left(\begin{array}{cc}x&0 \\y& x \end{array}\right)=2\left(\begin{array}{cc}10&6-x \\3&0 \end{array}\right)+\left(\begin{array}{cc}5&2x \\4& x \end{array}\right).

Evaluate x + y . x+y.


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

( x y 2 1 ) ( x 0 y x ) = 2 ( 10 6 x 3 0 ) + ( 5 2 x 4 x ) ( x 2 + y 2 x y 2 x + y x ) = ( 2 ( 10 ) + 5 2 ( 6 x ) + 2 x 2 ( 3 ) + 4 2 ( 0 ) + x ) = ( 25 12 10 x ) \begin{aligned} \begin{pmatrix} x & y \\ 2 & 1 \end{pmatrix} \begin{pmatrix} x & 0 \\ y & x \end{pmatrix} & = 2 \begin{pmatrix} 10 & 6-x \\ 3 & 0 \end{pmatrix} + \begin{pmatrix} 5 & 2x \\ 4 & x \end{pmatrix} \\ \begin{pmatrix} \color{#3D99F6}{x^2 + y^2} & \color{#D61F06}{xy} \\ 2x + y & x \end{pmatrix} & = \begin{pmatrix} 2(10)+5 & 2(6-x)+2x \\ 2(3)+4 & 2(0)+x \end{pmatrix} \\ & = \begin{pmatrix} \color{#3D99F6}{25} & \color{#D61F06}{12} \\ 10 & x \end{pmatrix} \end{aligned}

{ x 2 + y 2 = 25 . . . ( 1 ) x y = 12 . . . ( 2 ) \implies \begin{cases} \color{#3D99F6}{x^2 + y^2 = 25} & ...(1) \\ \color{#D61F06}{xy = 12} & ...(2) \end{cases}

( x + y ) 2 = x 2 + 2 x y + y 2 = 25 + 2 ( 12 ) = 49 x + y = ± 7 \begin{aligned} (x+y)^2 & = \color{#3D99F6}{x^2} + 2\color{#D61F06}{xy} + \color{#3D99F6}{y^2} = \color{#3D99F6}{25} + 2(\color{#D61F06}{12}) = 49 \\ \implies x+y & = \boxed{\pm 7} \end{aligned}

7 or -7 right

Joseph Press - 1 year, 4 months ago

Log in to reply

You are right.

Chew-Seong Cheong - 1 year, 4 months ago

Daniel Sugihantoro IT'S +7 OR -7

Abhinav AV - 1 year ago

If you solve for x and y, the only solutions are x=3 and y=4, therefore x+y will always be 7

Leonardo Dzib - 9 months, 4 weeks ago

How did you enter +- 7 into the answer field?

Piotr Kmiotczyk - 4 months, 4 weeks ago

I'll just show you how my work goes

right side

2 ( 10 6 x 3 0 ) + ( 5 2 x 4 x ) = ( 20 12 2 x 6 0 ) + ( 5 2 x 4 x ) = ( 25 12 10 x ) 2\begin{pmatrix} 10 & 6-x \\ 3 & 0 \end{pmatrix}\quad +\quad \begin{pmatrix} 5 & 2x \\ 4 & x \end{pmatrix}\\ =\begin{pmatrix} 20 & 12-2x \\ 6 & 0 \end{pmatrix}\quad +\quad \begin{pmatrix} 5 & 2x \\ 4 & x \end{pmatrix}\\ =\begin{pmatrix} 25 & 12 \\ 10 & x \end{pmatrix}

left side

( x y x 0 ) ( x 0 y x ) = ( x 2 + y 2 x y 2 x + y x ) \begin{pmatrix} x & y \\ x & 0 \end{pmatrix}\begin{pmatrix} x & 0 \\ y & x \end{pmatrix}\\ =\begin{pmatrix} { x }^{ 2 }+{ y }^{ 2 } & xy \\ 2x+y & x \end{pmatrix}

ending

( x 2 + y 2 x y 2 x + y x ) = ( 25 12 10 x ) x 2 + y 2 = 25 2 x + y = 10 x y = 12 ( x + y ) 2 2 x y = x 2 + y 2 ( x + y ) 2 2 × 12 = 25 ( x + y ) 2 = 49 x + y = 7 \begin{pmatrix} { x }^{ 2 }+{ y }^{ 2 } & xy \\ 2x+y & x \end{pmatrix}\quad =\quad \begin{pmatrix} 25 & 12 \\ 10 & x \end{pmatrix}\\ \\ { x }^{ 2 }+{ y }^{ 2 }\quad =\quad 25\\ 2x\quad +\quad y\quad =\quad 10\\ xy\quad =\quad 12\\ \\ { (x+y })^{ 2 }-2xy\quad =\quad { x }^{ 2 }\quad +\quad { y }^{ 2 }\\ { (x+y })^{ 2 }-2\times 12=25\\ { (x+y })^{ 2 }=49\\ x+y=7

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...